Sulfur/oxygen-doped porous carbons via NaCl-assisted thermolysis of a molecular precursor for CO2 capture - Zaman, Ali Can; Karaaslan, Omer Faruk (ELSEVIER SCIENCE SA, 2022)
A novel combination of a cheap, readily available and easy to synthesize molecular precursor: p-toluenesulfonic acid (TsOH) and pore former NaCl was utilized for the production of sulfur/oxygen doped carbons. Dynamic and statistic adsorption capability of carbons on major coal-fired power plant flue gas components (CO2 (Carbon dioxide), Nitrogen (N2) and water vapor (H2O)) and surface chemical properties were investigated. NaCl addition increases micropore and larger pore development, but it marginally affects CO2 capture performance at low pressures due to similar pore volumes of carbons at ultramicropore (0.7 nm) range. However, dynamic adsorption experiments revealed that presence of large pores increases kinetics of adsorption. NaCl addition positively influences CO2 capture performance beyond 0.4-0.5 bar. Maximum CO2 uptake values are in the range of 0.78 mmol g-1 at 0.15 bar (298 K). CO2 uptake at low pressures (0.15 bar) at 298 K is connected to pore volume of micropores that has equal or smaller dimeter than 0.5 nm. It was demonstrated that presence of nonoxidized sulfur on carbon surface has a positive effect on CO2 adsorption at 0.15 bar (298 K and 313 K). There is no correlation found between CO2 uptake and oxygen or oxidized sulfur content, but there is a negative correlation between oxidized sulfur and CO2/N2 selectivity.
Keywords: Microporous carbon; Molecular precursor; Surface chemistry; Template synthesis; METAL-ORGANIC FRAMEWORKS; ACTIVATED CARBON; NANOPOROUS CARBONS; SURFACE-CHEMISTRY; PORE-SIZE; ADSORPTION; NITROGEN; SULFUR; GRAPHENE; ADSORBENTS; Materials Science